Edukasi Pencegahan Stunting Pada Balita Keluarga Binaan Di Desa Uteunkot Kota Lhokseumawe - Mardiati, Mardiati; Khairunnisa, Cut; Vera Novalia (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2024)
Stunting continues to be a health issue that has not been effectively resolved in many regions of Indonesia, including Lhokseumawe. Lhokseumawe City's accomplishment of lowering the prevalence of stunting from 28.1% in 2021 to 20.7% in 2023 earned it the second-lowest stunting rate among all regions, following the Gayo Lues Regency. Although child stunting persists in Uteunkot Village, its prevalence is relatively small. This can be attributed to the lack of awareness among families and the community regarding the causes and preventive measures for stunting. This finding hinders the realization of “Lhokseumawe zero-stunting.” The purpose of this community service is to educate foster families in Uteunkot Village about the importance of preventing stunting among toddlers. Health education activities were delivered through a combination of interactive lectures, question-and-answer sessions, and the distribution of informative brochures. The results showed that the knowledge of foster family members increased after receiving education and brochures. The following advice is recommended for all foster family members in Uteunkot Village. To prevent stunting, ensuring proper nutrition during pregnancy and childbirth is crucial. Adequate nutrition is also vital for toddlers and children under the age of two. Providing education on stunting should be done continuously to the general public in an effort to disseminate information on stunting prevention.